Analisis Komparasi Efektivitas Iklan Pantene di Televisi dan YouTube Pada Masyarakat Kota Denpasar - Jelita Ananda, Ni Made Diah Ayu; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium, 2019)
ABSTRACT The effectiveness of advertising is a condition to what extent the effect of the message conveyed by an advertisement can attract attention, be understood, arouse emotions and move the target to respond in accordance with what is desired. The biggest contribution in the growth of television advertising industry spending in 2018 came from Pantene products. Pantene's massive television advertising expenditure was also accompanied by advertising on YouTube. This study aims to illustrate how the effectiveness of Pantene adverts on television and YouTube on the Denpasar City community compares. The3sampling=technique-in+this=study0is12non-probabilityDDsampling using purposive12sampling00method. The data in+thisPstudy were obtained byKLdistributingMKPquestionnairesBNKand measured usingL a Likert*scale. The8analysisPtechnique88used==in this study isKthe average calculation and=T-Test.WWTheBresultsSshowed3that2there9were(significantOdifferences_between Pantene ads on television and YouTube in the Denpasar City community.   Keywords : Pantene, Television Ads, YouTube Ads, Denpasar City Communities